Synthesis, characterization and antibacterial activity of nickel (II) and copper (II) complexes of N-(alkyl(aryl)carbamothioyl)-4-nitrobenzamide - Saeed, Sohail; Rashid, Naghmana; Ali, Muhammad; Hussain, Rizwan (European Journal of Chemistry, 2010)
Nickel and copper metal complexes of N-(R-carbamothioyl)-4-nitrobenzamide (R = diphenyl and ethylbutyl) were synthesized and characterized by IR, 1H NMR, mass spectrometry and elemental analysis. The spectroscopic data are consistent with the ligand and the metal complexes containing two O and S chelated ligands. N-(diphenylcarbamothioyl)-4-nitrobenzamide, HL1, was characterized by a single crystal X-ray diffraction study. It crystallizes in the triclinic space group P with unit cell dimensions of a = 6.8044(4) Å, b = 10.0113(6) Å, c = 13.2365(8) Å, α = 6.8044(4) °, β = 78.171(4) °, γ = 13.2365(8)°, V = 882.43(9) Å3. The ligands coordinate as bidentates yielding essentially neutral complexes of the type [ML2]. The ligands and complexes were screened for their in vitro antibacterial activities and comparatively the complexes showed greater antibacterial efficacy than the thiourea derivative ligands.